Trail running-management, organization, safety, evaluation. The activity of ITRA Association - Urbański, Robert (Journal of Education, Health and Sport, 2018)
Running is one of the most popular forms of physical activity. Lately, there is an increasing interest in mountain running, especially on ultra-distance. From year to year there is more running competitions organized in Poland and worldwide. Therefore, in the most popular mountain races, due to a dynamically growing number of applicants to participate in this type of sports rivalry, there is a necessity to hold drawings of the participants among those who had been previously verified. In 2013 International Trail Running Association (ITRA) started to operate. It was the first international organization that set itself the primary objective of development of this discipline of sport in a wider sense. Its main areas of activities are: the evaluation of the trail running (Endurance points, Mountain level, Performance index), improvement of quality of trail events and safety of its participants, preventive measures connected with the health of runners and doping, environmental protection, promotion and PR and international co-operation. Due to ITRA’s actions, in 2015 trail running was officially recognised by International Association of Athletics Federation (IAAF) as a discipline of athletics. The aim of this article is to present the actions taken by ITRA for the development of mountain running and their influence on the organization of running venues in Poland. The method and research material. The case study method has been used. The analysis was based on the documents and information provided and supported by ITRA organization and the institutional partners of the association. The research material also consisted of the competition rules certified by ITRA. Web portals and internet forums have been reviewed. Moreover, the social media on the subject of trail, ultra and mountain running have been monitored.